2020
DOI: 10.1021/acsami.9b21060
|View full text |Cite
|
Sign up to set email alerts
|

Does Bacterial Elasticity Affect Adhesion to Polymer Fibers?

Abstract: The factors governing bacterial adhesion to substrates with different topographies are still not fully identified. The present work seeks to elucidate for the first time and with quantitative data the roles of bacterial elasticity and shape and substrate topography in bacterial adhesion. With this aim, populations of three bacterial species, P. aeruginosa DSM 22644, B. subtilis DSM 10, and S. aureus DSM 20231 adhered on flat substrates covered with electrospun polycaprolactone fibers of different diameters ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 46 publications
1
18
0
Order By: Relevance
“…A multitude of different factors, including surface roughness and stiffness, feature geometry on a nano/microscale, and the subsequent available surface area, as well as chemical surface composition, contribute to bacterial adhesion. 5 Even though their general influence is well-established, 5 , 12 the mechanisms that determine the specific interaction of every individual factor with bacteria are still controversially discussed. As an example, for nanotopography and the resulting available surface area, it could be shown that increasing surface roughness and structures with feature sizes similar to bacteria support bacterial colonization.…”
Section: Introductionmentioning
confidence: 99%
“…A multitude of different factors, including surface roughness and stiffness, feature geometry on a nano/microscale, and the subsequent available surface area, as well as chemical surface composition, contribute to bacterial adhesion. 5 Even though their general influence is well-established, 5 , 12 the mechanisms that determine the specific interaction of every individual factor with bacteria are still controversially discussed. As an example, for nanotopography and the resulting available surface area, it could be shown that increasing surface roughness and structures with feature sizes similar to bacteria support bacterial colonization.…”
Section: Introductionmentioning
confidence: 99%
“…It is generally accepted [ 22 ] that an increase in the Young’s modulus, as a measure of the rigidity or elasticity of the cell wall, leads to a decrease in the adhesion efficiency of bacterial cells. However, in another study [ 7 ], treatment with hematite nanoparticles increased the rigidity of E. coli cells and caused the appearance of many adhesive sites on the cell surface.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, a less rigid and more flexible hydrophobic cell wall contributed to the uptake of hydrocarbon substrates by Rhodococcus cells [ 20 ]. Contradictory literature data on the influence of nanometals on mechanical and rheological properties of bacterial cells are partially explained by technical variations in the AFM nanoindentation and structural heterogeneity of the bacterial cell surface, represented by macromolecules with varying degrees of hydrophobicity, electric charge and spatial organization, causing heterogeneity of rheological properties [ 7 , 22 ]. The specific molecular interactions that cause these mechanical forces are the result of a complex interplay of fundamental hydrophobic, electrostatic, van der Waals and hydrogen bonding forces [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…56 It has recently been suggested that bacterial elasticity and shape may also govern bacterial adhesion to substrates. 57 subtilis. 58 PAN-based NFs also demonstrated low fouling values for B. subtilis.…”
Section: Articlementioning
confidence: 99%